PREPARATION, CHARACTERIZATION AND RELEASING -SWELLING KINETICS OF MYRRH BASED HYDROGEL - I. Hamodi, Mohammad; K. Younis, Mohammed (Science Journal of University of Zakho, 2023)
In this work, Myrrh gum was used with sodium alginate (SA) to create novel Myrrh-Alginate beads composite. These beads were produced utilizing the ionotropic gelation technique. Methylene blue (MB) was employed as a drug model to evaluate the kinetics of drug release and the capacity of the synthesized beads to function as a drug delivery system. The molecular interaction between sodium alginate and myrrh was confirmed by FTIR spectroscopy. The physical characteristics of the Myrrh-Alginate beads, including drug content, particle size, thermal properties, equilibrium water content (EWC), swelling behavior, and equilibrium swelling ratio (ESR), were studied to establish the hydrogel's response type, as well as the releasing kinetics at 37°C and in Phosphate buffer solution (PBS) at pH = 6.8 and 10. All beads (loaded and unloaded) were analyzed by Differential scanning calorimetry, Scanning electron microscopy (SEM) and X-ray diffraction analysis (XRD). The drug content percentages of the Myrrh-Alginate beads increased with a moderate fraction (5% ) of Myrrh but dropped with a higher Myrrh percentage. The Myrrh-Alginate beads absorbed more water and swelled more than the pure calcium alginate beads (S2) in pH 6.8 and 10 of (PBS). In a pH 6.8 of (PBS), the Myrrh-Alginate beads demonstrated a controlled and regulated style of releasing and demonstrated a high match with the Korsmeyer-Peppas model as they had the maximum values of the correlation factor (R2) in this model.
Keywords: hydrogel; drug delivery; Myrrh; swelling; releasing kinetics; methylene blue